The effect of divorce on income, housework time, social status and life satisfaction in China - Gao, Yingtao (Nanyang Technological University, 2021)
Divorce has become a growing social issue in China over the past few decades. Existing sociological studies have examined the patterns of divorce and have focused on the reasons for the increasing rates of divorce. However, the consequence of divorce for men and women in China has not received wide attention. Using longitudinal data from the China Family Panel Studies (CFPS) conducted between 2010 and 2018, I investigate the effect of divorce on four outcomes—income, housework time, perceived social status and life satisfaction. The thesis tests whether and how divorce affects these outcomes using both cross sectional and longitudinal analyses. In addition, the thesis focuses on gendered aspects of divorce and examines if divorce affects men and women differently. The key findings from the study are that divorce has a significant effect on all the four outcomes. Divorce has a positive relationship with income and a negative relationship with housework time, social status, and life satisfaction. The effect of divorce is gendered for some but not all the four outcomes. The findings add to the existing literature on the effect of divorce and are discussed by placing them in the context of China. The study’s findings reveal the multidimensional effect of divorce on different domains for men and women. The findings contribute to not only understanding marriage and family changes in China, but also enrich the current theoretical and empirical literature which have mostly been based on the western experience.